A Study on the Influence of Unsteady Forces on the Roll Characteristics of a Submarine during Free Ascent from Great Depth - Guo Xiang; Yongpeng Ou; Junjie Chen; Wei Wang; Hao Wu (Journal of Marine Science and Engineering, 2024)
The maximum diving depth of modern submarines has always been increasing. Although this has been useful and in some cases necessary, it usually comes with some risks. For instance, when a submarine encounters an emergency situation that requires immediate ascent from great depths, the situation becomes more dangerous, especially due to its rolling characteristics. To investigate the effect of unsteady forces during free ascent motion of submarines at great depths on submarine rolling, in this study, the SST-DDES model combined with the overset grid technique was used for the numerical simulation of a submarine free ascent. Water tank experiments for free ascent were conducted to validate the numerical approach, which confirmed the reliability of the numerical method. Following this, the CFD method was employed to conduct an initial exploratory investigation into the free ascent motion of deep-submergence submarines. The free ascent motion of submarines at great depths under five different degrees of freedom combinations was studied. The computational results indicated that submarines are more prone to roll over during free ascent at great depths. At a depth six times the length of the submarine, the maximum roll angle underwater reaches 22.8°. In addition, unsteady rolling moments, lateral forces, and yawing moments have a significant effect on submarine rolling, intensifying the tendency to roll. Furthermore, it was observed that the vertical hydrodynamic attack angle β is related to the rolling stability of the submarine, such that a moderate decrease in β is beneficial for the rolling stability. The numerical calculation method and preliminary research findings can provide theoretical support for controlling the ascent motion of real submarines.